Working with Nonprofit Organizations in Community Settings: Governance, Board Manual - Elizabeth B. Bolton; Lynda M. Spence (EDIS)
This is part of a series of 2-5 page fact sheets by Elizabeth B. Bolton and Lynda M. Spence that provide guidance for building a non-profit organization, from establishing its mission to effectively lobbying. Published by the UF Department of Family Youth and Community Sciences, June 2009. Reviewed June 2012.